Imprimer, collecter et concentrer l’image des villes : lieux d’édition et représentations urbaines en Europe (fin du XVe siècle-milieu du XVIIe siècle) - Eric Grosjean (Les Cahiers de l'École du Louvre)
From the sixteenth century onwards, with the development of printing, cities found new ways of representing themselves and widely disseminating the image they wished to project. Europe’s main publishing centres (Venice and Paris, for example) used the productivity of their printers to promote and disseminate their own image, and even to impose their vision on the rest of the community of European printers, authors and publishers. City views were intended to be more “realistic”, in other words, they sought to represent a vision like that which a physical observer outside the city would have had, in the form of a “portrait” from life. However, in Europe, a certain uniformity in the representations of cities in printed books set in during the sixteenth century. This standardisation was based on four factors: the renown and importance of the city in question, the presence of remarkable monuments that contributed to the immediate recognition of the city through its image and in themselves conveyed praise of the city, the existence of a production capacity for printed works that ensured the promotion and distribution of this representation, and the pre-existence of a large-scale plan or view of the city that served as a reference for European printed production.